ESTUDOS ESTRUTURAIS DA UROCANATO HIDRATASE DE Trypanosoma cruzi POR MÉTODOS EXPERIMENTAIS E COMPUTACIONAIS - Boreiko, Sheila (2014)
Chagas' disease, caused by the protozoan Trypanosoma cruzi, is one of the seventeen neglected diseases according to World Health Organization. In the last two decades, this parasite specific metabolic pathways have been evaluated as therapeutic targets, making the prospect for the development of more specific and less toxic drugs. To achieve this goal, there is the need for studies to get knowledge on the pathway protein three dimensional structures.Protein structures can be studied experimentally by the X ray diffraction technique and computationally by homology modeling, however, other structural information can also be obtained by spectroscopic techniques. Thus, in this work, structural studies of the enzyme Urocanate Hydratase from Trypanosoma cruzi (TcUH), which participates in the histidine metabolic pathway, were carried out. The enzyme was expressed functionally in E. coli and,by affinity chromatography, effectively purified and crystallized, however, no minimum quality for X-ray diffraction was observed. Thus, we carried out the structural study by circular dichroism (CD), small angle X-ray scattering (SAXS) and homology modeling. The TcUH is mainly composed of α-helices and its denaturation process by temperature starts near 50 ° C, being irreversible after completed. The SAXS study indicated that the protein in solution was not monomeric. With the homology produced model, docking studies indicated that some promising molecules to be carefully studied for possible inhibition tests.